Dystrophic Epidermolysis Bullosa in a Preschooler in a Middle Eastern Country - Harshita Prabhakaran MSN; Judie Arulappan PhD, DNSc; Sheeba Elizabeth J MSN; Sophia Cyril Vincent MSN (SAGE Publishing, 2023)
Epidermolysis Bullosa (EB) is a very rare genetic skin disorder associated with skin fragility. It results in blister formation on the skin. The purpose of this paper is to update the progress of a child with Dystrophic EB (DEB) who survived from infancy to preschool years and later died with recurrent skin blisters, bone marrow transplantation, and life support measures. A case analysis was done to evaluate the progress of the child. The mother of the child signed the written informed consent and granted permission to publish the details of the child with images and without disclosing the identifying information. The management of EB requires a multidisciplinary team approach. The care of the child should be aimed at protecting the child's skin from injury, nutritional support, meticulous wound care, and management of complications as required. The prognosis varies from case to case.